Bioprospection of diazotrophic bacteria from lemongrass and evaluation of its potential agricultural use (Revista Brasileira Multidisciplinar, 2026)
Lemon grass, a medicinal plant of economic interest, demands sustainability in the production of good quality raw materials, and resource optimization. Given this, it was aimed to evaluate the influence of diazotrophic bacteria on growth, and species development. The material collected was divided into sheet, profile, root, rhizome, and rhizospheric soil, isolated in semi -solids and semi -selective, JMV, LGI, JNFB, NFB, FAM, with three repetitions. After 15 days, the means that presented a characteristic film of the biological fixation of nitrogen were separated. The 86 isolates were grouped into a dendrogram, according to morphological characteristics, evaluating diversity, and 80% similarity, 23 strains were totaled. The experiment, conducted at a vegetation house from May 2022 to May 2023, had as treatment the 23 strains, positive control treatment, and negative control (without inoculation and without fertilization), totaling 25 treatments with 4 repetitions, in a randomized block design. The variables analyzed were green weight of the aerial part, green root weight, total weight, length length, root length, dry weight and root dry weight. All bacteria showed rapid growth and diversity among the characteristics, enabling high association capacity between the medicinal species and the various nitrogen -fixing bacterial species. The isolated BPCV, formed a microorganism collection bank, and the tested strains showed potential for use in lemon grass cultivation, replacing nitrogen fertilization, highlighting UNIFENAS 100-524, which was not higher in root growth only.
Keywords: medicinal plants; inoclating; essencial oils; biological fixation; growth promoters